Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan dan Kesiapan dalam Menghadapi Menarche di MIN Rejoso Peterongan Jombang - Mukhoirotin Mukhoirotin; Purniawati Nurul Qomari (Universitas Pesantren Tinggi Darul Ulum, 2017)
Abstrack Teenagers with low knowledge about menarche will suffer from anxiety, confusio, and fear so it can affect on their readiness to face menarche. So, it’s need the way to increasing the education and readines them about menarche with health education. The significance of this study to know about the influences of health education to the knowledge an readines to face menarche. In this research using design quasy experimental in pretest posttest one group design setting. Population is 53 respondents and put the sampel using random sampling technigue with sampel is 50 respondents. The independent variable in this research is the health eduation and the dependent varable of this research is knowledge and readines. The research instrument is using a quesioner. The data analysis which used is a Wilcoxon and Mann Whitney U test with a = 0,05. The result of wilcoxon test the variabels of knowledge and readiness p = 0,000 and the control’s group p = 0,498. And the readiness varuabel in ability’s group p = 0,00 and the control’s group p=0,660 show when p and readiness is p = 0,000. for the result of Mann Whitney U test in knowledge variabel p = 0,001 and the readines variabel p = 0,000. The result of this research is showing the influences of health education to the knowledge an readines to face. So, the scholl’s staff are suggested to make a connection in giving health education in scholl to develop the knowledge and readiness in to face Menarche. Keyword : Readiness, Menarche, Health Education, Knowledge